Influence of blade deformation on integral characteristic of axial flow fan - Eberlinc, Matjaž (Strojniški vestnik, 2008)
Axial flow fan blades deform during operation due to the various forces that act on them. That is why, we can ask ourselves about the influence of the blade deformation on the integral and local characteristics. In the paper, we present a study of influence of axial flow fan blade deformation. The paper deals with measurements of the blade deformation at the known integral working conditions. Results - deformations of fan blade tip were used for numerical study of the influence of the changed blade form on the fan's aerodynamic characteristic. Fan integral characteristics were measured in accordance with the ISO-DIS 5801:2006 standard and were carried out on the wind tunnel of the Hidria Institute Klima, Godovie. Other measurements of the blade deformation were done on the measuring station on the Faculty of Mechanical Engineering, University of Ljubljana, with the help of computer aided visualization. Deformations were measured in three working points, whichwere defined with fan integral parameters. Results of the measurements helped to determine modified form of the blade, which was then used for the numerical simulation for the same fan integral parameters. The study of deformation influence, based on the numerical simulation, was carried out.
Keywords: aksialni ventilatorji; lopatice; deformacije; vizualizacija